2012
DOI: 10.1164/rccm.201105-0939pp
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Anxiety and Depression on Chronic Obstructive Pulmonary Disease Exacerbation Risk

Abstract: Chronic obstructive pulmonary disease (COPD) exacerbations contribute significantly to morbidity and mortality. COPD is also associated with high levels of psychological distress, which has been linked with higher exacerbation rates. At a recent American Thoracic Society conference symposium titled "Depression and Obstructive Lung Disease: State of the Science and Future Directions" held in 2010 in New Orleans, clinicians and researchers identified a number of important research priorities related to psychiatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
128
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 42 publications
3
128
1
4
Order By: Relevance
“…Patients with more than one of these coexisting psychological disorders and low socioeconomic status have even higher readmission rates, suggesting the additive effect of these factors on readmission rates, as noted in earlier studies. 9,37,38 Moreover, these factors explained a large proportion of variation in 30-day readmission rates. These psychological disorders are more likely to predict 30-day readmission than other significant factors like male sex and measures of disease severity such as length of hospital stay, ICU stay, and use of mechanical ventilation during the index hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with more than one of these coexisting psychological disorders and low socioeconomic status have even higher readmission rates, suggesting the additive effect of these factors on readmission rates, as noted in earlier studies. 9,37,38 Moreover, these factors explained a large proportion of variation in 30-day readmission rates. These psychological disorders are more likely to predict 30-day readmission than other significant factors like male sex and measures of disease severity such as length of hospital stay, ICU stay, and use of mechanical ventilation during the index hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…20 Lack of community resources to meet the transportation needs or clinic copayment may play a role in clinic absenteeism. Less than one-third of readmissions are related to acute exacerbation of COPD; the remainder are related to other comorbidities, 37,39 and the number of comorbidities correlates directly with frequency of 30-day readmission. 16,18,40,41 The complex overlap of symptoms with COPD creates challenges for the diagnosis and treatment of comorbid psychological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies examining the prospective associations between clinical levels and symptoms of psychological distress and exacerbation risk for patients with COPD [9,10,[23][24][25][26][27][28][29] were recently evaluated in a review paper [8]. Three of those studies evaluated outpatients [23][24][25], whereas one included a cohort of elderly medical patients including non-COPD patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…COPD patients often face major physical impairment and embarrassing symptoms [5], while depression by itself is also aggravated by worsening dyspnoea and fatigue, diminishing functional performance and exercise capacity, and is associated with impaired quality of life [6]. Depression is additionally related to AECOPD frequency, with frequent exacerbators presenting higher depression scores compared with infrequent exacerbators [7,8]. Although it has been reported that depressed COPD patients experience longer hospitalisations for AECOPD [9], the impact of depressive symptoms on the recovery and outcomes from an AECOPD has not been thoroughly studied.…”
mentioning
confidence: 99%
“…Given that reducing 30-day readmission for acute exacerbation of COPD is now a target set forth by the Centers for Medicare and Medicaid Services, these studies, together with our data, support the need for further research, including testing of pharmacologic and behavioral interventions, to examine psychological comorbidities such as depression as potentially modifiable risk factors for readmission for acute exacerbation of COPD. Anxiety has also been linked to a worse sensation of dyspnea in COPD (47) and increased risk of acute exacerbation of COPD (36,47), but data on the risk of readmission are limited. Although we found an association between anxiety and readmissions on univariate analysis, this did not remain significant after multivariable modeling.…”
Section: Original Researchmentioning
confidence: 99%